Early Lopinavir/ritonavir does not reduce mortality in COVID-19 patients: Results of a large multicenter study. Issue 6 (June 2021) - Lora-Tamayo, Jaime; Maestro, Guillermo; Lalueza, Antonio; Rubio-Rivas, Manuel; Villarreal Paul, Gracia; Arnalich Fernández, Francisco; Beato Pérez, José Luis; Vargas Núñez, Juan Antonio; Llorente Barrio, Mónica; Lumbreras Bermejo, Carlos; ,
Highlights: This is the largest study assessing the efficacy of LPV/r against SARS-CoV-2. The overall use of LPV/r was not associated with lower mortality in CoVID19 patients. The early use of LPV/r (median 5 days) showed no benefit either.